Earlier translation of evidence into public subsidy may prevent morbidity and mortality: an example using statins in diabetics with normal cholesterol levels - Michael M. Page; Frank M. Sanfilippo; Elizabeth A. Geelhoed; Tom G. Briffa; Michael S.T. Hobbs (Elsevier, 2012)
Abstract Objective : To determine the effects on cardiovascular outcomes and costs of a delay in subsidising statins for Australian normolipidaemic diabetics aged 60-79 years that occurred between 2002 and 2006. Methods : The Australian normolipidaemic diabetic population aged 60-79 with no history of coronary heart disease (CHD) or stroke was estimated from the Australian Bureau of Statistics (National Health Survey 2001 and 2002 population estimates). The number of CHD and stroke events expected to have occurred between 2002 and 2006 were estimated from the United Kingdom Prospective Diabetes Study Risk Engine. The proportion of these events that may have been prevented by the use of statins in this population was estimated using risk reduction values from the Heart Protection Study. Results : The target population was estimated as 186,501. In this population, 3,205 (95% confidence interval (CI) 2567, 4003) CHD events, of which 1,456 (95% CI 908, 2334) would have been fatal, could have been prevented if all patients had been treated with statins. In addition, 2,150 (95% CI 1515, 3052) ischaemic strokes could have been prevented. The net cost to the government would have been about $136 million per year over the four‐year period. Conclusions : Delays in the adoption of statins on the Pharmaceutical Benefits Scheme based on evidence available at the time for specific populations may have led to preventable morbidity and mortality. Implications The effects of delays in translating new evidence into public subsidies for drugs are measurable and are likely to be significant.